MENGENALKAN BERAGAM PROFESI ORANG TUA PADA ANAK KELAS 1 MELALUI GAMBAR VISUAL DAN BERCERITA - Imawati, Ida Ayu Putu Febri; Noviana, Ni Luh Putu Risma; Dika, I Wayan (Sewagati, 2024)
The introduction and socialization of parents' professions at SD Negeri 3 Belega is part of the introduction to the school environment. The introduction of parents' professions aims to foster their understanding of the diversity of roles in society and appreciate the contribution of each profession. The introduction of this profession is full of meaning that can direct children regarding their interests and future goals. The introduction of this profession is carried out using interesting visual presentation media and storytelling. The results of this activity illustrate that the students of SD Negeri 3 Belega have been able to understand the basic concepts of parents' professions and even tell stories about the professions of their parents and the people around them. The approach of interesting visual images and storytelling is suitable for learning because it increases enthusiasm, active interaction, and interest in further exploration of children.